Myocardial steatosis and left ventricular contractile dysfunction in patients with severe aortic stenosis. - Mahmod, M; Bull, S; Suttie, J; Pal, N; Holloway, C; Dass, S; Myerson, S; Schneider, J; De Silva, R; Petrou, M; Sayeed, R; Westaby, S; et al. (2013)
BACKGROUND: Aortic stenosis (AS) leads to left ventricular (LV) hypertrophy and dysfunction. We hypothesized that cardiac steatosis is involved in the pathophysiology and also assessed whether it is reversible after aortic valve replacement. METHODS AND RESULTS: Thirty-nine patients with severe AS (symptomatic=25, asymptomatic=14) with normal LV ejection fraction and no significant coronary artery disease and 20 age- and sex-matched healthy controls underwent cardiac 1H-magnetic resonance spectroscopy and imaging for the determination of steatosis (myocardial triglyceride content) and cardiac function, including circumferential strain (measured by magnetic resonance tagging). Strain was lower in both symptomatic and asymptomatic AS (-16.4 ± 2.5% and -18.1 ± 2.9%, respectively, versus controls -20.7 ± 2.0%, both P<0.05). Myocardial steatosis was found in both symptomatic and asymptomatic patients with AS (0.89 ± 0.42% in symptomatic AS; 0.75 ± 0.36% in asymptomatic AS versus controls 0.45 ± 0.17, both P<0.05). Importantly, multivariable analysis indicated that steatosis was an independent correlate of impaired LV strain. Spectroscopic measurements of myocardial triglyceride content correlated significantly with histological analysis of biopsies obtained during aortic valve replacement. At 8.0 ± 2.1 months after aortic valve replacement, steatosis and strain had recovered toward normal. CONCLUSIONS: Pronounced myocardial steatosis is present in severe AS, regardless of symptoms, and is independently associated with the degree of LV strain impairment. Myocardial triglyceride content measured by magnetic resonance spectroscopy correlates with histological quantification. Steatosis and strain impairment are reversible after aortic valve replacement. Our findings suggest a novel pathophysiological mechanism in AS, myocardial steatosis, which may be amenable to treatment, thus potentially delaying onset of LV dysfunction.